POLITISASI ISLAM PADA MASA KESULTANAN BANTEN - MAFTUH AJMAIN (IAIN Syekh Nurjati Cirebon, 2022)
This article focuses on the discussion of Islamic teachings that were used for political purposes during the Sultanate of Banten. The sultans of Banten, in order to perpetuate their power, often used terms taken from Islam or words derived from Arabic. Their original names were originally taken from non-Arabic languages and changed to Arabic names, such as Hasanuddin whose real name is Sabakingkin. Therefore, it is necessary to explore how the Banten kingdom adopted Islamic teachings in carrying out its government and what the further implications for the people of Banten are. As an essay that seeks to reveal past events, this paper uses the historical method whose data is obtained from library sources, among others. At the end of the discussion, this article concludes that the kingdom of Banten changed the names of non-Arab kings to Arabic names. This can be seen, for example, in the name of the founder of the Banten kingdom, Hasanuddin. Hasanuddin was originally named Prince Sabakingking. Then, royal titles also use Arabic terms, such as Maulana or Sultan. To get the title of sultan, the king sent a special envoy to Mecca with the aim of meeting with the Great Sharif. Thus, the first king to receive the title of sultan was Sultan Abdulmafakhir Mahmud 'Abdul Qadir (1596-1651), who was subsequently used by the kings after him. Sultan Abdul Qadir's real name is Prince Ratu. These royal policies which were thick with Islam, furthermore, had implications for the people of Banten. The people of Banten are known as people who are fanatical about Islam and find it more difficult to accept new things that come from outside.